2019
DOI: 10.1111/1467-9566.12896
|View full text |Cite
|
Sign up to set email alerts
|

A sociology of public responses to hospital change and closure

Abstract: The “problem” of public resistance to hospital closure is a recurring trope in health policy debates around the world. Recent papers have argued that when it comes to major change to hospitals, “the public” cannot be persuaded by clinical evidence, and that mechanisms of public involvement are ill‐equipped to reconcile opposition with management desire for radical change. This paper presents data from in‐depth qualitative case studies of three hospital change processes in Scotland's National Health Service, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The following is from an interview with Stephen and illustrates the activities of Medical Directors on the ‘back stage’ of healthcare planning. In the UK hospital closures are a politically contested issue, often the focus of ‘save our hospital’ campaigns from local community groups ( Stewart 2019 ). In this case plans to close hospital facilities had been prepared by the organisation as part of financial assurance processes requested by a national regulator.…”
Section: Introductionmentioning
confidence: 99%
“…The following is from an interview with Stephen and illustrates the activities of Medical Directors on the ‘back stage’ of healthcare planning. In the UK hospital closures are a politically contested issue, often the focus of ‘save our hospital’ campaigns from local community groups ( Stewart 2019 ). In this case plans to close hospital facilities had been prepared by the organisation as part of financial assurance processes requested by a national regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Interview data are supplemented with analysis of official board documents, CIC empirical studies (published and unpublished), emails and written correspondence. These data were collected between February 2018 and July 2019, as part of a broader 4 year interpretive study of four 'change projects' in the Scottish NHS (Stewart, 2019). Ethical approval for the study was received from the University of Edinburgh's Usher Institute Research Ethics G. The CIC case was added 'asymmetrically': first as an atypical example where patients come from all over Scotland but which is not designated a national service and, second, because our reading of the sociology of CAM indicated that the case might yield a clash of 'knowledges' at the fringes of mainstream healthcare.…”
Section: Study Background and Methodsmentioning
confidence: 99%
“…Second, we survey existing work on the legitimacy/legitimation of CAM, which focuses on the actions of practitioners. We bring the CAM 'consumer' into the frame, actively shaping the trajectory of their NHS (Stewart, 2016(Stewart, , 2019. The third empirical section examines campaigners' work in legitimating CAM, drawing on both experiential knowledge and that credentialed by experts.…”
Section: Introductionmentioning
confidence: 99%
“…81 The Targeted Enhanced Recruitment Scheme has been highly successful in increasing the number of general practitioner trainees moving to under-doctored locations in return for a one-off 'golden handshake'. 82 This suggests that closing hospitals on the pretext of inadequate staffing is a short-term, nihilistic solution to a problem that, although urgent, is not without alternative solutions.…”
Section: The Problem Of Workforcementioning
confidence: 99%